(untitled) (Research, Society and Development, 2020)
The building construction is responsible for the largest industrial sectors in the world, with high energy demand and use of natural resources. Given the scarcity of natural resources and the energy crisis, the use of waste in building materials becomes a target. Therefore, this study aimed to evaluate different treatments with pine sawdust and coffee husk additions, both at 10% by mass and also evaluated in drying and burning. The treatments were evaluated by bulk density, linear shrinkage and compressive strength. In the treatments without burning, it was possible to verify that the addition of 10% of residue reduces the mechanical resistance of the material considerably but improves the physical properties. In the burned materials, it was observed that the addition of residues is unsatisfactory due to the high temperature, carbonizing them, increasing the porosity, thus destabilizing the material, negatively affecting the physical and mechanical properties.